2020
DOI: 10.1038/s41467-020-18885-9
|View full text |Cite
|
Sign up to set email alerts
|

Leptin alters energy intake and fat mass but not energy expenditure in lean subjects

Abstract: Based on studies in mice, leptin was expected to decrease body weight in obese individuals. However, the majority of the obese are hyperleptinemic and do not respond to leptin treatment, suggesting the presence of leptin tolerance and questioning the role of leptin as regulator of energy balance in humans. We thus performed detailed novel measurements and analyses of samples and data from our clinical trials biobank to investigate leptin effects on mechanisms of weight regulation in lean normo- and mildly hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 84 publications
(128 reference statements)
2
35
1
Order By: Relevance
“…There are demonstrable differences in leptin biology between animals and humans. In contrast to data from animal studies, leptin treatment does not affect sympathetic nervous system activity, heart rate, or blood pressure (14). The study also identified putative binding sites for p50 and p65 at the CpG sites for Trpm7; therefore, other transcription factors like NFB may also modulate leptin-mediated Trpm7 expression.…”
contrasting
confidence: 76%
“…There are demonstrable differences in leptin biology between animals and humans. In contrast to data from animal studies, leptin treatment does not affect sympathetic nervous system activity, heart rate, or blood pressure (14). The study also identified putative binding sites for p50 and p65 at the CpG sites for Trpm7; therefore, other transcription factors like NFB may also modulate leptin-mediated Trpm7 expression.…”
contrasting
confidence: 76%
“…2 ). In normal weight subjects [ 25 ] and in patients with lipodystrophy [ 26 ] metreleptin can induce weight loss via a reduced appetite/hunger.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a large number of leptin targets and the different pathways in which it is implicated could explain the wide range of observed metabolic effects that ultimately allow us to adapt to the different nutritional scenarios. Regardless of the broad evidence implicating leptin in the context of NAFLD/NASH development, especially in the research with animal models, the story in humans is different [ 285 ] and more studies are needed. For instance, instead of descriptive results, interventional and controlled studies using leptin or leptin antagonists may help to clarify its role in NAFLD and to evaluate its potential use as a treatment or biomarker of the disease, either at initial steps or at more advanced levels such as NASH with or without fibrosis.…”
Section: Discussionmentioning
confidence: 99%